BS EN 61786-1 Ed.1.0 Amd.1. Measurement of DC magnetic; AC magnetic and AC electric fields from 1 Hz to 100 kHz with regard to exposure of human beings. Part 1. Requirements for measuring instruments (21st April 2022) - British Standards Institution,
No abstract available